Improvement in Quality of Life with OnabotulinumtoxinA for Cervical Dystonia: POSTURe. (21st September 2021) - Petitclerc, Marc; Cloutier, Martin; Naud, Pierre; Langlois, Mélanie; Bhogal, Meetu; Davidovic, Goran
ABSTRACT: Introduction: Symptoms of cervical dystonia (CD) can vary in severity and cause significant pain. OnabotulinumtoxinA is an approved treatment for CD. This study assessed health-related quality of life (HRQoL) in patients with CD who received multiple onabotulinumtoxinA treatments. Methods: This prospective, observational standard-of-care study was conducted at multiple neurology centers in Québec, Canada. Patients reported the health impact of CD using the Cervical Dystonia Impact Profile (CDIP)-58, before and after up to eight onabotulinumtoxinA treatments. Other measures included the Cervical Dystonia Severity Rating Scale by physician, employment status using the Work Productivity Questionnaire and pain using the Pain Numeric Rating Scale (PNRS). Adverse events (AEs) were recorded. Results: Sixty-two patients were enrolled (safety population, n = 61; modified efficacy population, n = 58). Participants were mostly females who were employed; most (79.3%) had torticollis. In all, 21/62 patients (33.9%) discontinued the study. At the final visit, there was a statistically significant ( p < 0.001) improvement in all eight CDIP-58 subscales, particularly head and neck symptoms (−31.0) and psychosocial functioning (−28.2). Employment increased from baseline (55%) to the end of the study (64%), and there was improvement in work productivity. There was a significant ( p < 0.0001) reduction in pain measured by the PNRS, from −0.5 post-treatment 1 to −2.4 at end of study. AEs (neck pain, muscular weakness, dysphagia, nausea) were consistent with onabotulinumtoxinA use. Conclusion: These real-world data indicate that after repeated, long-term use, onabotulinumtoxinA continues to be a safe and effective treatment for CD, improving HRQoL and work productivity.